The Effects of Astaxanthin on Metabolic Syndrome: A Comprehensive Review - Chunhao Gao; Nengyun Gong; Fangtian Chen; Shiran Hu; Qingxin Zhou; Xiang Gao (Marine Drugs, 2024)
Metabolic syndrome (MS) represents a complex cluster of metabolic disorders primarily characterized by obesity, insulin resistance, hyperglycemia, dyslipidemia, hypertension, and hyperuricemia. Diet and functional ingredients play a pivotal role in seeking non-pharmacological strategies to prevent and ameliorate MS. Astaxanthin (AST), a carotenoid found in various marine organisms, exhibits exceptional antioxidant properties and holds great promise as a natural compound that improves MS. This article introduces the basic properties of AST, including its absorptance and metabolic pathways, along with various isomers. Most importantly, we comprehensively review the effects and mechanisms of AST on improving the primary components of MS. These mechanisms primarily involve regulating signal transduction, transport, or metabolic pathways within the body, as well as influencing intestinal microbiota and metabolites, thereby exerting positive effects on metabolism and inhibiting the occurrence of MS. This review emphasizes the potential efficacy of AST in managing MS. However, more studies are needed to confirm the clinical effect of AST on MS and reveal potential molecular mechanisms.